LOCAL IDENTITY CONSIDERATION IN MAINTAINING PLACE BRANDING SUSTAINABILITY (THE CASE OF INDONESIA) - Forina Lestari; Melasutra MD Dali; Norbani Che-Ha (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The development of place branding has increased in various parts of the world. Competition in attracting investment, tourists, and other resources encourages city managers to think hard in order to be able to sell their potentials and uniqueness. Local identity is considered as one of the uniqueness that may attract people and money. This study will focus on the extent to which local characteristics and culture of the local community are considered in the formation of the city identity. The study undertook a content analysis of around thirty literature of city branding development in Indonesia, both national and international journals, to gain insight into the particular issue. The results of the study show that the imagery of cities in Indonesia is generally still limited to the formation of slogans and logos, which pay little attention to the cultural elements and aspirations of the local community. As a result, several cities had to replace their slogan and logo within a few years due to public criticism.